PENGARUH PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION BERBANTUAN MEDIA ANIMASI TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMP NEGERI 1 BATU LAYAR - Maliki, Imam Maksum Al; Doyan, Aris; ‘Ardhuha, Jannatin (Lensa : Jurnal Kependidikan Fisika, 2014)
This study is a quasi experimental study that aims to determine the effect of using direct instruction model with animation media to the academic achievement of physiscs in student class VIII SMP Negeri 1 Batu Layar. The population in this study were all students of class VIII SMP Negeri 1 Batu Layar that were 87 students. Whereas the students of class VIIIA which are 22 students as the experimental group and 22 students of class VIIIC as a control group. Sampling methode was random cluster sampling. The Research design using pre-test - post-test control group design. Based on Pre-test result, the average mark of class VIIIA and class VIIIC were 24.70 and 28.95, respectively. Post-test result gave the information that the average mark of class VIIIA and class VIIIC were 79.29 and 71.62 respectively. Research hypotesis was analyzed using polled varians t-test. It can be concluded that there was a different in physics academic achievement between experimental group and control group, where the experimental group using direct  instruction model with animation media as the treatment and the control group using direct instruction only. The academic achievement of experimental group were better than control group, it can be a reason to say that the treatment by using direct instruction model with animation media gave the positive effect to the academic achievement of physiscs in student class VIII SMP Negeri 1 Batu Layar.